Towards a TREK-1/2 (TWIK-Related K+ Channel 1 and 2) dual activator tool compound: Multi-dimensional optimization of BL-1249. Issue 13 (1st July 2019) - Iwaki, Yuzo; Yashiro, Kentaro; Kokubo, Masaya; Mori, Takahiro; Wieting, Joshua M.; McGowan, Kevin M.; Bridges, Thomas M.; Engers, Darren W.; Denton, Jerod S.; Kurata, Haruto; Lindsley, Craig W.
Graphical abstract: Highlights: First detailed SAR account around TREK1/2 activators. First optimization campaign directed at BL-1249. Discovery of new in vitro and in vivo tool compound, ONO-2960632/VU6011992. Abstract: This letter describes a focused, multi-dimensional optimization campaign around BL-1249, a fenamate class non-steroidal anti-inflammatory and a known activator of the K2P potassium channels TREK-1 (K2P 2.1) and TREK-2 (K2P 10.1). While BL-1249 has been widely profiled in vitro as a dual TREK-1/2 activator, poor physicochemical and DMPK properties have precluded a deeper understanding of the therapeutic potential of these key K2P channels across a broad spectrum of peripheral and central human disease. Here, we report multi-dimensional SAR that led to a novel TREK-1/2 dual activator chemotype, exemplified by ONO-2960632/VU6011992, with improved DMPK properties, representing a new lead for further optimization towards robust in vivo tool compounds.